2014
DOI: 10.1007/s10995-014-1524-x
|View full text |Cite
|
Sign up to set email alerts
|

Do Black–White Racial Disparities in Breastfeeding Persist in the Military Community?

Abstract: We conduct a comparative analysis of breastfeeding behavior between military and civilian-affiliated mothers. Our focus is on African American mothers among whom breastfeeding rates are lowest. The military context may mitigate conditions associated with low breastfeeding prevalence by (a) providing stable employment and educational opportunities to populations who face an otherwise poor labor market and (b) providing universal healthcare that includes breastfeeding consultation. Using pregnancy risk assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
1
4
1
Order By: Relevance
“…Furthermore, racial and ethnic minorities were not associated with being food-insecure, which differs from national trends ( 1 , 43 ) . This suggests that the military environment mitigates racial and ethnic influences on food security status; this pattern has been seen in other research where racial gaps in breast-feeding rates were minimized among the military population ( 35 ) .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Furthermore, racial and ethnic minorities were not associated with being food-insecure, which differs from national trends ( 1 , 43 ) . This suggests that the military environment mitigates racial and ethnic influences on food security status; this pattern has been seen in other research where racial gaps in breast-feeding rates were minimized among the military population ( 35 ) .…”
Section: Discussionsupporting
confidence: 67%
“…Conversely, the military may provide a setting where traditional demographics associated with food insecurity, such as race and ethnicity, may be less influential. For instance, a study by Lundquist et al found that racial gaps in breast-feeding rates were minimized among the military population ( 35 ) .…”
mentioning
confidence: 99%
“…Although this sample of veterans had a relatively high rate of breastfeeding at 4 weeks, they also experienced a racial disparity in breastfeeding between black and white veterans. This contradicts Lundquist et al’s (2015) findings, which indicated that the racial disparity in breastfeeding between African American and white mothers was significantly reduced among military populations. Researchers who studied other health conditions have shown that racial health disparities are reduced among veterans using VA health care.…”
Section: Discussioncontrasting
confidence: 65%
“…An alternative explanation is that despite the greater access to healthcare in the military (Lundquist et al 2015), ex-offenders face a greater risk of mortality than non-offenders because they have less protective capacity against the high burden of disease, such as drug overdose, violence, and injury (Binswanger et al 2007;Travis et al 2014). Insights from the civilian world suggest that marginalized communities with limited resources and grim employment prospects are willing to take on dangerous tasks and deadly work (Levitt and Venkatesh 2000;Purser 2012), which likely aggravates the risks of injury and death.…”
Section: Discussionmentioning
confidence: 99%